Method of estimation of environmental hazard of urban land using for vital activity of population - Tretiak, A.; Tretiak, N.; Kirova, M. (Land Management, Cadastre and Land Monitoring, 2018)
Ensuring environmental safety remains the main way of solving ecological problems, which guarantees citizens the development and living in harmony with the environment and opens up new opportunities for other forms of activity in the field of nature management, in particular, political, economic, social, etc. In particular, to assess the adequacy of the urban land use structure with the requirements of environmental safety, trends in the land fund structure changes in the city are studied. Accordingly, the ratio of total land area and land for functional use for each urban area is an important indicator of the state of environmental safety. Among the many issues related to ensuring the ecological safety of urban land use, the problems of substantiation of ways and areas of ecologization in the conditions of market transformations become especially relevant, because the structure of urban land use is characterized by different levels of anthropogenic loading in accordance with the typing of land in terms of economic use. Optimal land use, unlike rational, provides for the establishment of environmentally appropriate and economically advantageous relations between different types and subtypes of land use, which, in turn, depend on types of land and land with different functional uses. The ecological danger of urban land use is the level of possible negative changes in the components of the process of land and nature use and the process of consumption of environmental services in the urban environment. The essence of the dangers of urban land use is manifested in the objective existence of probable negative changes that can lead to environmentally hazardous consequences that restrict or exclude the effective use of natural goods in the city. Identification of definitions of ecological safety and the danger of urban land use makes it possible to characterize them as two polar states, the transition from one state to another occurs when the appropriate limit - the loss of the properties of land use to withstand the internal and external man-made hazards. The article illustrates the relation between ecological safety and danger as the opposite of urban land use in the context of determining the necessary system of measures. In our opinion, the diagnosis and indication of ecological safety of urban land use, as the basic basis for the health of the urban population, is characterized by a system of indicators, which include environmental sustainability of land use, anthropogenic load of the territory and the level of environmental risk of land use. Therefore, a methodology for assessing the ecological danger and anthropogenic loading of land use within the territories of cities is proposed. In particular, for urban land use, the classification of land for functional use is expanded in order to assess the state of the environmental hazard. In accordance with the improved classification, the value of the ecological stability coefficient and the values of the estimation points of anthropogenic loading of land and land for functional use are developed. The ecological stability of land use and the level of anthropogenic loading depend on the structure of land use on the functions of land use. In order to assess the ecological hazard, it is proposed to apply an ecological hazard ratio, as an indicator of changes in its state, calculated by subtraction from the unit of the ecological stability coefficient. The scale of the environmental hazard of land use is developed on the basis of the ecological hazard rate as an indicator of changes in its state. The calculations carried out according to the proposed method show that the situation with the ecological state in the context of the districts of the city of Kiev is very complicated (in the 5 districts of the city the situation is environmentally unstable). It is proved that the level of ecological danger of land use in the context of the districts of the city of Kiev is closely intertwined with the level of anthropogenic load (in 5 districts it is characterized as critical). Thus, the threats to the environmental instability of land use, and, consequently, to the environmental safety of the city’s population, remain, indicating a lack of land use change over the years. Key words: environmental safety, urban land using, environmental hazard assessment, land using typology of green plantations.